Lorenz meets rating but misses valuation - Eva Camacho Cuena; Christian Seidl (Kiel University, Department of Economics, 2005)
Using an experiment with material incentives, this paper investigates the violation of Lorenz relations in the case of dominant and single-crossing Lorenz curves. Our experimental design consists of two treatments: an income distribution treatment and a lottery treatment. Both treatments were conducted in Italy and Spain. In each treatment, subjects were asked to judge ten multiple-outcome lotteries or ten n-dimensional income distributions in terms of both ratings and valuations. This 2 2 2 experimental design, allows us to investigate the response-mode (rating versus valuation) and framing (lotteries versus income distributions) effects in subjects' perceptions concerning the two types of Lorenz relations. We found the existence of a marked response-mode effect, as only the ratings of the lotteries and income distributions confirm both Lorenz relations, whereas the valuations violate them. The framing effect is significant only for the Spanish data. For this data the sign of the framing effect depends on the type of the Lorenz relation considered. For crossing Lorenz curves, a higher conformity corresponds to the lottery frame, for Lorenz dominance a higher conformity corresponds to the income distribution frame.
Keywords: D31; C91; D81; D63; 330; Income Distributions; Lotteries; Lorenz Curves; Inequality and Risk Aversion; Response?Mode Effects; Einkommensverteilung; Wahrnehmung; Lorenz-Kurve; Präferenztheorie; Spieltheorie; Experiment; Spanien; Italien; framing